Synthesis of esters of emoxypine - Лисовская, Maryna V.; Kvasyuk, Evgeny I. (Journal of the Belarusian State University. Ecology, 2019)
A new and effective method for preparation of esters of emoxypine as potentially having increased permeability of the Blood-Brain Barrier was developed. Some new (2-ethyl-6-methylpyridine-3-yl)butandioat derivatives 13–16 were obtained by condensation of emoxypine 3 with previously synthesized n-butyl, n-amyl, i-amyl and benzyl monoesters of succinic acid 4, 6–8 in presence of dicyclohexycarbodiimide or by reaction of sodium salt of emoxypine with chloroanhydride of corresponding esters. The structures of synthesized compounds were confirmed by UV-, IR-, NMRspectroscopy and mass-spectrometry.
Keywords: emoxypine; 2-ethyl-6-methylpyridine-3-ol; hydroxypyridine; lipophilic derivatives; spectroscopy